Strain and defect engineered monolayer Ni-MoS2 for pH-universal hydrogen evolution catalysis. Issue 39 (1st October 2019) - Liang, Dan; Zhang, Yong-Wei; Lu, Pengfei; Yu, Zhi Gen
Abstract : The demonstrated monolayer Ni-MoS2 possesses a high HER performance in both acidic and alkaline solutions. Abstract : The sustainable production of H2 fuel via the hydrogen evolution reaction (HER) using low-cost catalysts to replace expensive noble metals is highly desired. Here using first-principles calculations, we design a delicate monolayer transition metal compound, Ni-MoS2, consisting of orderly interlaced Ni and Mo metal ions, and investigate its HER catalytic performance. The Gibbs free energy, Δ G H, which is the best descriptor for the HER, is calculated and optimized with respect to strain and S vacancies. Remarkably, the calculated Δ G H is found to be ∼0 eV at the biaxial strain of 11%−12%, which is superior to MoS2, for which straining alone is insufficient to achieve the optimal performance. We further reveal that along with straining, the bandgap is reduced and a semiconductor-to-metal transition is induced, leading to an enhancement in the charge transfer and HER performance. Moreover, Δ G H ≈ 0 eV is achieved at the S vacancy concentration of only ∼2.5%, which is in strong contrast to ∼12.5% required for MoS2 . We further show that the defective Ni-MoS2 is able to enhance the conductivity, which leads to the reduction of Δ G H . Two remarkable HER mechanisms and alkaline HER kinetics have been demonstrated in this study: perfect Ni-MoS2 prefers the Volmer–Heyrovsky mechanism in the strain state, whereas the Volmer–Tafel mechanism is more preferred for the defective Ni-MoS2 . The kinetic energy barrier of the alkaline HER is reduced, revealing that Ni-MoS2 promotes the rate-determining water dissociation step. The present work suggests that the designed monolayer Ni-MoS2 compound significantly outperforms MoS2 in terms of HER activity, and thus is promising for low-cost, pH-universal and high-performance HER applications.